Physiological resistance responses of rice plant (Oryza sativa) provided with silicate fertilizer to sheath blight disease (Rhizoctonia solani) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Azizah R, Rachmawati D. 2023. Physiological resistance responses of rice plant (Oryza sativa) provided with silicate fertilizer to sheath blight disease (Rhizoctonia solani). Biodiversitas 24: 3785-3795. Sheath blight disease that is caused by the fungus Rhizoctonia solani Kühn generally leads to the reduction of rice yields. The application of silicate fertilizers can increase the resistance to pathogens. This research aimed to determine the effect of silicate fertilizer application on the physiological resistance responses of rice plants to R. solani, the primary pathogen responsible for rice sheath blight. This study used three rice cultivars with different resistance levels to sheath blight, including Pandan Wangi (resistant), Cisadane (susceptible), and IR64 (moderately resistant), which were treated with three doses of silicate fertilizer 0 kg ha-1, 200 kg ha-1 and 400 kg ha-1 with sheath blight inoculation and without inoculation. The results showed that Pandan Wangi provided with 200 kg ha-1 silicate fertilizer produced the highest reduction in the percentage of relative lesion height (RLH), and the application of 400 kg ha-1 silicate fertilizer had a greater positive effect of reducing the lesion in Cisadane and IR64. In susceptible and moderately resistant cultivars, Cisadane and IR64, higher doses of silicate fertilizer have a better effect on strengthening plant tissue during inoculation treatments. The application of 400 kg ha-1 silicate fertilizer without inoculation significantly affected relative water content. In the moderately resistant cultivar IR64, the silicate fertilizer played a role in the physiological response by strengthening the plant tissue, as indicated by the increasing lignin content, sclerenchyma and cuticle thickness.
Keywords: Cultivars, physiological resistance, sheath blight disease, silicate fertilizer